(untitled) (Management and Connections Journal, 2026)
The virtual environment has emerged as a new and potential workspace in light of the proliferation of social media. Significant discussions on the platformization of work have been developed within the field of Organizational Studies. Among the activities arising in this context, the present study focuses on digital content creation. It aimed to understand the experiences of pleasure and suffering among content creators on social media under the dominant technical logic. A qualitative study was conducted using in-depth interviews and secondary data collection. The findings indicate that although content creation is often portrayed as the myth of the perfect job: fun, free, glamorous, and well-paid; in reality, it unfolds within a dynamic of both pleasure and suffering, mediated by algorithms whose performance rules are neither clear nor accessible to workers. In this way, it reinforces the perception of content creation as a form of entrepreneurship and a dynamic of self-exploitation in work.